1967
DOI: 10.1111/j.1365-2621.1967.tb01321_32_3.x
|View full text |Cite
|
Sign up to set email alerts
|

Tenderness and Associated Characteristics of Stretched and Contracted Bovine Muscles

Abstract: SUMMARY— The effects of muscle contraction state, carcass maturity, and post‐mortem aging (4°C) on tenderness were studied on excised semitendinosus muscles of six A‐ and six E‐maturity bovine carcasses. Fiber diameter was shown to be curvilinearly related with sarcomere length (R = .95 and .87 for A‐ and E‐maturity groups, respectively). As muscles were shortened they had a larger percent area of fibers and a smaller percent area of both edomysial and perimysial material. Muscles of the A‐maturity group were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0
2

Year Published

1973
1973
2014
2014

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 136 publications
(28 citation statements)
references
References 23 publications
2
24
0
2
Order By: Relevance
“…In fact, Herring, Cassens, Suess, Brungardt & Briskey (1967) found that there was a curvilinear relationship between sarcomere length and tenderness, and thus they concluded that it would be more critical to prevent post mortem shortening than to ensure a maximum stretch. Further, they found fewer stretching effects on shear force and tenderness scores and a greater variability in shear force values in stretched beef muscles (semitendinosus) from older animals (E-maturity; USDA, 1997) than in muscles from young animals (A-maturity; USDA, 1997) possibly due to different connective tissue contents and its flexibility (Herring et al, 1967). In that regards, speculated that limited or no influence of 4S on meat tenderness could be due to a higher initial background toughness of meat from older animals.…”
Section: Shear Forcementioning
confidence: 95%
“…In fact, Herring, Cassens, Suess, Brungardt & Briskey (1967) found that there was a curvilinear relationship between sarcomere length and tenderness, and thus they concluded that it would be more critical to prevent post mortem shortening than to ensure a maximum stretch. Further, they found fewer stretching effects on shear force and tenderness scores and a greater variability in shear force values in stretched beef muscles (semitendinosus) from older animals (E-maturity; USDA, 1997) than in muscles from young animals (A-maturity; USDA, 1997) possibly due to different connective tissue contents and its flexibility (Herring et al, 1967). In that regards, speculated that limited or no influence of 4S on meat tenderness could be due to a higher initial background toughness of meat from older animals.…”
Section: Shear Forcementioning
confidence: 95%
“…In general, shortening is recognised as one of major contributors to decreased meat tenderness, where the shorter the sarcomere, the tougher the meat (Marsh and Leet 1966;Herring et al 1967;Tornberg 1996). Furthermore, the detrimental impact of heat shortening on meat tenderness has been reported (Marsh and Leet 1966;Davey and Gilbert 1973;Bowling et al 1978;Lee and Ashmore 1985;Hertzman et al 1993;Geesink et al 2000).…”
Section: Influence Of Sarcomere (Heat) Shortening On Tendernessmentioning
confidence: 99%
“…Macfarlane, Harris, and Shorthose (1974) highlighted that another approach to preventing muscle shortening is to restrain muscles physically until they are in rigour mortis. Many studies such as Locker (1960) ;Herring, Cassens, Suess, Brungardt, and Briskey (1967); Davey, Kuttel, and Gilbert (1967); Devine, Payne, and Wells (2002) and Troy (2006) have proven the concept that pre-rigour excised muscles could be stretched in various ways with resultant improvements in tenderness.…”
Section: Introductionmentioning
confidence: 97%